Endometrial thickness is associated with low birthweight in frozen embryo transfer cycles: A retrospective cohort study of 8,235 singleton newborns - He, Tingting; Li, Mingzhao; Li, Wei; Meng, Peng; Xue, Xia; Shi, Juanzi (Frontiers in Endocrinology, 2022)
Objective: To explore the association between endometrial thickness (EMT) and adverse neonatal outcomes in frozen in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET) cycles. Methods: This retrospective study involved a total of 8,235 women under the age of 35 years who underwent IVF/ICSI cycles and received frozen embryo transfer (FET) at a tertiary-care academic medical from January 2015 to December 2019, resulting in a live singleton newborn. Patients were categorized into three groups depending on EMT: ≤7.5 mm, 7.5-12 mm and >12 mm. The primary outcome was low birthweight (LBW). The secondary outcomes were preterm birth (PTB), small-for-gestational age (SGA), large-for-gestational age (LGA) and high birthweight (HBW). Result(s): Compared with EMT >7.5–12 mm group, the risk of being born LBW was statistically significantly increased in the EMT ≤7.5 mm group (adjusted odds ratio [aOR] 2.179; 95% confidence interval [CI], 1.305–3.640; P=.003), while dramatically decreased in the EMT >12 mm group (aOR 0.584; 95% CI, 0.403-0.844; P=.004). Moreover, newborn gender and pregnancy complications were all independent predictors for LBW. Furthermore, a significant decrease in birthweight was found in the EMT ≤7.5 mm group as compared with EMT >7.5–12 mm group and EMT >12 mm group (3,239±612 vs. 3,357±512 and 3,374±479 g, respectively), and similar result was found in term of gestational age (38.41±2.19 vs. 39.01±1.68 and 39.09±1.5 weeks, respectively). Conclusion(s): After frozen IVF/ICSI-ET, EMT ≤7.5 mm is independently associated with increased risk of LBW among women with singleton newborns. Therefore, we suggest that women with EMT ≤7.5 mm after achieving pregnancy by IVF/ICSI-ET treatment should warrant more attention to reduce the risk of delivering a LBW newborn.